AMPS-1D Simulation of P3HT Solar Cells: Impact of HOMO-LUMO Offset, Thickness, Temperature, and Optical Bandgap on Performance - Al-Otaibi, Hadab; Eid, Omer I.; Eisa, M. E. M.; Alzahrani, Amwaj N. (Engineering, Technology & Applied Science Research, 2024)
This study employed the AMPS-1D software to investigate the relationship between the open-circuit voltage (Voc) and the energy difference between the Highest Occupied Molecular Orbital (HOMO) of the donor and the Lowest Unoccupied Molecular Orbital (LUMO) of the acceptor in P3HT:PCBM bulk heterojunction organic solar cells. The findings indicate a correlation between Voc and the HOMO-LUMO offset up to 1.1 eV, after which Voc remains constant. This behavior is further elucidated using a theorem based on the quasi-Fermi level, which predicts a Voc of 0.64 V, in good agreement with our simulation result of 0.68 V. The Power Conversion Efficiency (PCE) of the solar cell was studied with respect to the active layer thickness, demonstrating an increase in PCE up to 0.40 μm followed by a decrease, yielding a maximum PCE of 5.023%, consistent with the literature. The effect of temperature on PCE was also examined, demonstrating an increase in PCE with decreasing temperature in the range of 150–320 K, with a performance of 6.371% at 150 K. Furthermore, the impact of the optical bandgap on PCE was explored, showing that the PCE increased with a decrease in the optical bandgap of the P3HT:PCBM solar cell, reaching 9.94% when the optical bandgap was 1.5 eV. These findings provide valuable insights into the optimization of the performance of organic solar cells by manipulating key parameters, such as the HOMO-LUMO offset, active layer thickness, temperature, and optical bandgap.